Crystal Structures of Sulfobetaine-8 Solvates: Bend Hydrophobic Chains and Doubly Charge-Assisted Hydrogen Bonds N+CH⋯−O3S - Andrei V. Churakov; Denis V. Anokhin; Paulina Kalle; Marina A. Kiseleva; Mikhail V. Vener; Lyudmila G. Kuz’mina (Crystals)
Three novel solvatomorphs (C13H29NO3S•CH3OH, 1; C13H29NO3S•0.113(H2O), 2; C13H29NO3S•0.038(H2O), 3) of zwitterionic sulfobetaine-8 were obtained and their structures were determined using single-crystal X-Ray diffraction. In all cases dimethyl–amino substituted hydrophobic chains -(CH2)3-N+Me2-(CH2)7-Me exhibit kinks at nitrogen atoms resulted from strong intra- and intermolecular CH⋯O hydrogen bonds between negatively charged sulfonic anion -O3S- and positively charged tetraalkylammonium fragments. Periodic (solid state) DFT calculations for structure 1 showed that the energy of the intermolecular hydrogen bonds CH…O is very high, at about 17 kJ/mol. In hydrates 2 and 3, water molecules play the structure-forming role since they interconnect hydrophobic layers by HOH…-O3S hydrogen bonds. The location of only partially occupied water molecules in the interlayer space leads to low stability of both crystals 2 and 3 in open air.